Case report: a genomics-guided reclassification of a blood culture isolate misassigned by MALDI-TOF as Yersinia pestis. Issue 10 (3rd October 2022) - Sim, Eby M.; Koh, Bryant; Ng, Jimmy; Nguyen, Trang; Wang, Qinning; Ginn, Andrew N.; Brown, Mitchell; Pham, David; Sintchenko, Vitali
Abstract : In this report, we describe a case where Gram-negative rods were isolated from a blood culture which subsequently presented a discordant Yersinia species result by MALDI-TOF. Rapid sequencing provided high-resolution identification of the isolate as Yersinia pseudotuberculosis, which was subsequently confirmed by biochemical tests.